2006
DOI: 10.1007/s00422-006-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear causality between signals: methods, examples and neurophysiological applications

Abstract: Definition of Granger Causality Coefficients. The two signals x(t i), i.e. ipsi-lateral LFP) and y(t i), i.e.contra-lateral LFP, (sampled at t i = 0, ∆t, ..., (N − 1)∆t, where N = 3.6 × 10 5) are modelled by a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 66 publications
1
139
1
4
Order By: Relevance
“…Geweke [13] was the first to propose a linear bivariate time-series approach assessing linear Granger causality (LGC) based on the prediction error variance of the time series associated with a statistical test for causality [12]. If process X 2 has no causal influence on process X 1 , then LGC X 2 →X 1 becomes close to zero, which means that the knowledge of past values of X 2 does not improve the prediction of X 1 , but if LGC Bassani et al [15] estimated the direct causal coupling by applying two GC approaches (the F-test and the Wald test) along the baroreflex in two anaesthesiological procedures.…”
Section: (I) Linear Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geweke [13] was the first to propose a linear bivariate time-series approach assessing linear Granger causality (LGC) based on the prediction error variance of the time series associated with a statistical test for causality [12]. If process X 2 has no causal influence on process X 1 , then LGC X 2 →X 1 becomes close to zero, which means that the knowledge of past values of X 2 does not improve the prediction of X 1 , but if LGC Bassani et al [15] estimated the direct causal coupling by applying two GC approaches (the F-test and the Wald test) along the baroreflex in two anaesthesiological procedures.…”
Section: (I) Linear Methodsmentioning
confidence: 99%
“…This is associated with various delays and is able to determine whether the causal relation between two nonlinear signals (x, y) is coupled directly or mediated by another process [12]. Here, the extended Granger causality index (EGCI) y→x was introduced as a function of δ (neighbourhood size).…”
Section: (I) Linear Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Granger causality 2 refers to a family of synchrony measures that are derived from linear stochastic models of time series; as the above linear interdependence measures, they quantify to which extent different signals are linearly interdependent (see (Granger , 1969;Kamiński et al, 1991Kamiński et al, , 2005Gourévitch et al, 2006;Korzeniewska et al, 2003;Eichler, 2006;Blinowska et al, 2004;Ancona et al, 2004;Astolfi et al, 2004Astolfi et al, , 2005Schelter et al, 2005;Chen et al, 2006) for detailed information about Granger causality). Whereas the linear interdependence measures of Section 2.1 to 2.4 are bivariate, i.e., they can only be applied to pairs of signals, Granger causality measures are multivariate, they can be applied to multiple signals simultaneously.…”
Section: Granger Causalitymentioning
confidence: 99%
“…Although PDC has proved to be an accurate tool for the detection of direct connectivities, both in cases of coupled oscillators (Baccalá and Sameshima 2001;Winterhalder et al 2005;Gourévitch et al 2006;Schelter et al 2006a) or simple neuronal models of interconnected neurons (Sameshima and Baccalá 1999;Kamiński et al 2001;Astolfi et al 2007), it has been shown that large differences in the variances of the modeled time series can yield distortions in the resulting PDC values (Winterhalder et al 2005;Baccala et al 2007). For example, a set of three uncorrelated white noise processes, where two of them have much larger variance than the third, will produce a distorted connectivity profile, since PDC wrongly detects connections from the low-variance process to the other two (Winterhalder et al 2005).…”
Section: Partial Directed Coherencementioning
confidence: 99%